Design, Synthesis, and Quorum Quenching Potential of Novel Catechol–Zingerone Conjugate to Find an Elixir to Tackle Pseudomonas aeruginosa Through the Trojan Horse Strategy - Mangal, Surabhi; Dua, Tamanna; Chauhan, Monika; Dhingra, Neelima; Chhibber, Sanjay; Singh, Vasundhara; Harjai, Kusum (Frontiers in Chemistry, 2022)
To address the issue of multidrug resistance in Pseudomonas aeruginosa, a novel catechol–zingerone conjugate (1) linked via a non-hydrolyzable 1,2,3-triazole linker was synthesized and subjected to biological evaluation based on the Trojan horse strategy. To enhance the efficacy, catechol, a xenosiderophore, utilized by P. aeruginosa for iron assimilation, and the dietary phytochemical zingerone, known for its anti-virulent activity against Pseudomonas aeruginosa, were exploited in the present study. Theoretical validation of conjugate (1) was conducted by in silico molecular docking analysis to determine the interaction with outer membrane transport receptor PirA and quorum sensing signal receptors. In addition, nine-fold binding affinity of Conjugate (1) toward PirA (5FP2) in comparison to its natural ligand catechol with D-score −1.13 Å authenticated the designed Trojan horse drug. Conjugate (1) showed stronger anti-virulent activity than zingerone; hence, it exhibited a promising anti-biofilm efficacy as assessed by crystal violet assay and visualized by FESEM toward P. aeruginosa. Encouraging results against P. aeruginosa in terms of quorum sensing regulated virulence factors, motility phenotypes, and biofilm formation with no cell cytotoxicity and could help open hitherto unexplored possibilities of establishing Trojan horse drugs as a successful approach against multidrug resistance in P. aeruginosa.